Field‐assisted thermionic emission toward quantitative modeling of charge‐transfer mechanisms in contact electrification. Issue 4 (7th February 2022) - Xia, Xin; Wang, Haoyu; Zi, Yunlong
Abstract: Charge transfer mechanisms of contact electrification (CE) are essential for widening applications of the triboelectric nanogenerator, and thus are widely studied by scientists around the world. However, the quantitative modeling of CE, especially that between polymers, is still lacking. Herein, a model was proposed to describe the contributions from different mechanisms, including electron transfer and mass transfer in polymer/polymer CE through the field‐assisted thermionic emission, where three groups of charge transfer mechanisms were distinguished by the polarity of the charge transfer and the corresponding electric field. The results indicated that the total generated charge in CE is actually much larger than the measured net surface charge, confirming the bidirectional material‐dependent charge transfer mechanisms between two surfaces, which is meaningful for understanding the millennium puzzle in triboelectrification and provides a new perspective for promoting the applications to tailor surface charge generation. Abstract : Contact electrification (CE) is a universally existed charge transfer phenomenon between any materials in contact. During CE, both positive and negative charges, including electrons and ions/materials are bidirectional transferred between the two surfaces. Through the field‐assisted thermionic emission, three groups of charge transfer mechanisms are distinguished by the polarity of the charge transfer and the corresponding electric field.